Interactive effects of temperature, nutrient level and sandprawns (Kraussillichirus kraussi) ecosystem engineering on microplankton community structure - Ogunnusi, Oluwasegun (Department of Biological Sciences, 2025)
Global warming and eutrophication are leading global change stressors that threatened coastal environments. Water quality degradation has gained scientific attention in particular, especially from the perspective of finding nature-based solutions (NBS) to microbiological proliferation. Endobenthic crustaceans (including Southern African sandprawns: Kraussillichirus kraussi) and microorganisms have proven to be an effective nature-based tools to improve and monitor coastal water quality respectively. Previous research has proposed that the below-ground burrow systems of K. kraussi function as a biofiltration system, whereby active bi-directional water pumping by sandprawns causes phytoplankton cells to be adsorbed onto the walls of their burrows, thus assisting in limiting phytoplankton proliferation associated with eutrophication. However, little quantitative research has been done on the hypothesized biofiltration effects of sandprawns and their burrow systems on microbial assemblages inhibiting the overlying water column. This rationale formed the basis of my research, which aimed to experimentally quantify the effects of common sandprawns on pelagic bacterial assemblages in a global change context. This was achieved using a six-week laboratory mesocosm experiment, with each experimental mesocosm being half-filled with water and sediment collected from Zandvlei Estuary and divided into three treatments of varying natural sandprawn densities (0% (control), 50% and 100%), temperature (13.6oC and 29.4oC) and eutrophication (meso- and eutrophic) levels. At the end of the experiment, water column DNA was collected through a size- fractionated filtration process for DNA extraction followed by 16S rRNA amplicon analysis and metagenomic sequencing was carried out. Results indicate that the bacterial communities from the experiment were dominated by Proteobacteria (84.65%), but Margulisbacteria (0.002%) was the least abundant. Multivariate analysis demonstrated that the interactions between (1) sandprawn density and trophic state and (2) sandprawn density and temperature significantly explained bacterial variance. Notably, increasing sandprawn abundance induced a pelagic bacterial assemblage shift, with the most discriminating taxa being Citrobacter freundii and the Enterobacterales. A significant sandprawn-induced reduction in the abundance of Escherichia-Shigella coli was irrespective of the nutrient and temperature levels; these bacteria are indicators of coastal water quality and human health risk. Ecosystem engineering by K. kraussi thus reduced abundance of many waterborne pathogens (E. coli., Enterobacter spp.), but other taxa became more abundant with increasing sandprawn density. Common sandprawns and their habitats should be conserved to assist in averting the proliferation of some waterborne pathogenic microbes (E. coli). This study supports the use of sandprawns (and similar endobenthic engineers) as a NBS to control the proliferation of waterborne bacteria. However, further research is necessary to understand the consequences of increasing abundances of some bacterial taxa with sandprawn density.